Generalized topologies of single-stage input-current-shaping circuits. - Huber, L. (IEEE Transactions on power electronics)
In this paper, two generalized topologies of single-stage input-current-shaping (S2ICS) circuits are derived: S2 ICS circuits with two-terminal ICS cells and S2ICS circuits with three-terminal ICS cells. It is shown that most of the recently published S2ICS circuits belong to either of the two generalized topologies. It is also shown that the two generalized S2ICS topologies are functionally equivalent. Based on the generalized approach, a few new S2ICS circuits are developed. Experimental results obtained on a selected pair of S2ICS circuits with two-terminal and three-terminal ICS cells are also provided